Brain-derived neurotrophic factor serum levels as a candidate biomarker for withdrawal in crack heroin dependence - Enam Alhagh Charkhat Gorgich; Mohammad Gol Rigi; Hamed Fanaei; Houman Parsaei; Abdolhakim Ghanbarzehi (BMC, 2024)
Abstract Background Crack heroin is a novel opiate derivative with highly addictive properties and unfamiliar health consequences. It causes a variety of brain dysfunctions that are mediated by neurochemical alterations and abnormal neuroplasticity. Brain-derived neurotrophic factor (BDNF) is a widely recognized biological marker implicated in the neuropathology of substance use during substance use disorder and withdrawal. Its involvement can significantly contribute to the severity of withdrawal symptoms. Hence, this study aimed to evaluate BDNF levels in crack heroin users before and after withdrawal. Methods In this cross-sectional study, 148 male participants were recruited and divided into two groups: persons with crack heroin use disorder (n = 74) and the controls (n = 74). The BDNF serum levels were measured in both crack heroin users and control groups upon hospitalization and again after twenty-one days of withdrawal using the enzyme-linked immunosorbent assay. Results The results demonstrated that BDNF levels in persons with crack heroin use disorder upon admission were significantly lower than the levels observed upon discharge and in the control group (p < 0.05). Additionally, a significant difference in BDNF levels was found between persons with crack heroin use disorder at admission and discharge (p = 0.038). Furthermore, BDNF levels showed an inverse correlation with the daily dose of substance use (r= -0.420, p = 0.03) and the duration of crack heroin use (r= -0.235, p = 0.001). Conclusions A progressive increment in BDNF levels during early detoxification is associated with the daily amount of substance use and the duration of substance use. Our findings suggest that changes in BDNF serum levels during crack heroin use disorder and withdrawal could serve as potential biomarkers for assessing the intensity of withdrawal symptoms and substance use-related behaviors.